Measuring and managing franchisee satisfaction : a study of academic franchising / Firdaus Abdullah ... [et al.] - Abdullah, Firdaus; Alwi, Mohd Rashidee; Voon, Boo Ho; Lee, Nagarajah (Institute of Research, Development and Commercialization (IRDC), 2008)
This study attempts to explore different approaches of franchisee satisfaction within an academic setting, develop and validate a new measuring instrument, examine the key factors and their influence on performance and intention to remain in the network and eventually manage the franchise network for longterm continuity. This study was conducted in Malaysia over a sample of 68 respondents representing 19 franchised colleges within Universiti Teknologi MARA's (UiTM) network. The findings suggest five dimensions of franchisee satisfaction namely social interaction, service support, financing, assurance and competence. Hence, UiTM should be able to ascertain the level of services provided. and to determine which dimensions need improvement. Knowing the strengths and weaknesses ofthese dimensions and their relative influence may result in better allocation of resources so as to provide a better service to the franchised colleges . This study has also sought to contribute further to the growing literature on franchising by advancing a new 23-item measuring instrument, which is specifically tailored for academic franchising. Such valid and reliable measuring scale would be a tool that tertiary institutions could use to improve their performance in the light of increased competition with the development of global academic franchising.